O ensino híbrido suplementar e a aprendizagem móvel de embriologia com o uso de um blog - Eliel Ribeiro do Nascimento (2020)
The Digital Technologies of Information and Communication - DTIC comprise several tools that offer advantages in the educational context, especially for high school youth, most of them so-called “digital natives”. Among these possibilities is the use of cell phones, as a strategic tool in the hybrid teaching of Embryology content. In schools, the greatest difficulties in the study of this theme are mainly related to the understanding of understanding complex, microscopic and extremely dynamic processes that occur on a three-dimensional plane and that are usually demonstrated only in two-dimensional images projected or present in textbooks, thus losing understanding process space. Given this scenario, the objective of the present work was to develop a didactic sequence (DS) with the insertion of an interactive blog that can be accessed by cell phones or smartphones, by students and teachers, for the hybrid teaching of Embryology, as part of the Biology of Development which studies the various biological equipment related to the formation of the living being. For the development of the work, we counted on a class of 34 students of the 2nd year of high school from a public school located in the region of Barreiro, south zone of Belo Horizonte. Initially, through a questionnaire, a survey of previous knowledge about the content of Embryology was carried out. Initially, through a questionnaire, a survey of previous knowledge about the content of Embryology was carried out. Subsequently, the activities proposed in a DS continued: screening of a film with an emphasis on the scientific method; two technical visits, the first at the Museum of Morphological Sciences and the second at NEDUCOM (Center for Education and Communication in Life Sciences), both spaces at UFMG; Survey of hypotheses in an inverted classroom and a comparative embryology class. All activities served as support to prepare students in the development of mass modeling or Biscuit models. To finish the DS students should answer the learning questionnaire and the satisfaction questionnaire. The data from the questionnaires were analyzed in a quantitative and qualitative way and synthesized in a word cloud and, for data analysis of the reports, the qualitative analysis technique proposed by Lüdke & André was applied, in addition to notes of the observations of the researcher professor, compiled in a field notebook throughout the process. The interactive blog was developed based on the main doubts raised in the survey of students' previous knowledge, in the models developed by them, as well as with the collaboration of a focus group, composed of 2 students from the 3rd year of high school and made available by the teacher researcher for access via cell phone, in the classroom or at a distance, as part of the teaching-learning process of hybrid teaching. It was not possible to apply DS completely due to the problem of the corona virus pandemic, but the analysis of the reports presented, and the data collected through the field notebook allowed us to infer that most students were motivated with the activities developed, with emphasis to non-formal spaces, which have given meaning to the content of Embryology for their lives.